Sir Cumference and all the king's tens : a math adventure - Neuschwander, Cindy (Charlesbridge, 2009)
When Sir Cumference and his wife, Lady Di of Ameter, host a massive surprise birthday party for the king, they must figure out quick a way to count all the guests in attendance.